Unsphered, Disorbed, Decentred: Shakespeare's Astronomical Imagination. (2nd October 2021) - Cetera-Włodarczyk, Anna; Hope, Jonathan; Włodarczyk, Jarosław
ABSTRACT: Recent findings by historians of science focus on London at the turn of the seventeenth century as one of the most fascinating places to investigate the reception of the new astronomy propelled by the Copernican revolution and observational discoveries. However, literary critics and editors typically place Shakespeare's imagery within the geocentric model of the universe, firmly anchored in the medieval paradigm, denying any impact of the new models of cosmos on his ingenuity. Drawing on the cumulative argument derived from the history of astronomy and literary linguistic analysis, we argue that Shakespeare's references to the unsphered and disorbed planets and stars are better understood when viewed in the light of the disputes of the times, the decline of the concept of the celestial orbs in particular. The simplified and much overused dichotomy between geo- vs. heliocentrism does not give justice to the complex intellectual climate of the late sixteenth century and obscures the imaginative power of these references. Our essay foregrounds the influence and instability of the competing worldviews, the specificity of London astronomical inquires, and the consistency of Shakespeare's recurrent representations of cosmic disruptions.